MicroRNAs Regulating Mitochondrial Function in Cardiac Diseases - Zhang, Guang-Qiong; Wang, Sheng-Quan; Chen, Yan; Fu, Ling-Yun; Xu, Yi-Ni; Li, Ling; Tao, Ling; Shen, Xiang-Chun (Frontiers in Pharmacology, 2021)
Mitochondria are the key organelles that supply cellular energy. As the most active organ in the body, the energy required to maintain the mechanical function of the heart requires a high quantity of high-quality mitochondria in cardiomyocytes. MicroRNAs (miRNAs) are single-stranded noncoding RNAs, approximately 22 nt in length, which play key roles in mediating post-transcriptional gene silencing. Numerous studies have confirmed that miRNAs can participate in the occurrence and development of cardiac diseases by regulating mitochondrial function-related genes and signaling pathways. Therefore, elucidating the crosstalk that occurs between miRNAs and mitochondria is important for the prevention and treatment of cardiac diseases. In this review, we discuss the biogenesis of miRNAs, the miRNA-mediated regulation of major genes involved in the maintenance of mitochondrial function, and the effects of miRNAs on mitochondrial function in cardiac diseases in order to provide a theoretical basis for the clinical prevention and treatment of cardiac disease and the development of new drugs.